Factor Analysis of Determinants Influencing the Use of Implant Contraception among Women of Reproductive Age - Mulyadi Paramata; Herlina Yusuf; Sunarto Kadir (GLOBAL HEALTH SCIENCE GROUP, 2026)
Implant contraceptives are long-acting reversible methods intended to prevent pregnancy and are considered highly effective and non-permanent. Implants can provide protection for three to five years with a failure rate of only 0.05 per 100 users, achieving effectiveness of up to 99%. However, the utilization of implant contraception remains influenced by various factors. This study aimed to analyze the factors influencing the use of contraceptive implants among couples of reproductive age in the working area of the Kabila Community Health Center. This study employed an analytical observational design with a cross-sectional approach. The research was conducted in the working area of the Kabila Community Health Center, Bone Bolango Regency, from April to May 2025. A total of 173 respondents were selected using a simple random sampling technique. Data were collected using a structured questionnaire that had been validated through expert judgment and item–total correlation analysis and demonstrated good reliability with a Cronbach’s alpha value greater than 0.70. The data were analyzed using the chi-square test. The results showed that visits by family planning officers (ρ = 0.000), availability of contraceptives (ρ = 0.029), and contraceptive service costs (ρ = 0.000) were significantly associated with the use of contraceptive implants. This study concludes that family planning officer visits, contraceptive availability, and service costs are significant factors influencing the use of contraceptive implants among couples of reproductive age in the working area of the Kabila Community Health Center, Bone Bolango Regency.